2017
DOI: 10.1017/s1041610217001028
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Care Mapping in long-term care settings: a systematic review of the evidence

Abstract: Available research provides preliminary evidence that Dementia Care Mapping may benefit care workers and people living with dementia in care settings. Future research should build on the successful studies to date and use other outcomes to better understand the benefits of this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…As in previous studies, we have connected our outcome measures to the claim that DCM increases job satisfaction. Studies on DCM that aimed at dementia care staff found improved caring skills, leading to increased job satisfaction, which included a tendency of reduced stress, burnout and emotional exhaustion as well as less negative and more positive reactions to clients, although this was not significant (Barbosa et al, ). DCM may thus indirectly improve some negative work experiences but its effects may be too weak to improve job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As in previous studies, we have connected our outcome measures to the claim that DCM increases job satisfaction. Studies on DCM that aimed at dementia care staff found improved caring skills, leading to increased job satisfaction, which included a tendency of reduced stress, burnout and emotional exhaustion as well as less negative and more positive reactions to clients, although this was not significant (Barbosa et al, ). DCM may thus indirectly improve some negative work experiences but its effects may be too weak to improve job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the two previous studies to assess the effect of DCM on dementia care staff both made use of experienced mappers, but offering either one (Jeon et al, 2012) or two DCM cycles with newly trained mappers (Van de Ven et al, 2013). None of them found significant effects on job satisfaction and care skills, but they found improvement of negative work experiences (Jeon et al, 2012;Van de Ven et al, 2013;Barbosa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dementia Care Mapping (DCM) is a widely used method to support staff working in dementia care in psychogeriatric nursing homes (Barbosa, Lord, Blighe, & Mountain, 2017;Chenoweth et al, 2009;Jeon et al, 2012;Kuiper, Dijkstra, Tuinstra, & Groothoff, 2009;Rokstad et al, 2013;Van de Ven, 2014). It is promising for staff working with older people with intellectual disability and has a number of characteristics that are innovative for this field: it is a relatively structured psychosocial method, it is based on principles of person-centred care, and it is specifically aiming at people with dementia (Finnamore & Lord, 2007;Jaycock, Persaud, & Johnson, 2006;Persaud & Jaycock, 2001;Schaap, Dijkstra, Finnema, & Reijneveld, 2017).…”
mentioning
confidence: 99%